Peningkatan Keaktifan Belajar dan Hasil Belajar Siswa melalui Model Pembelajaran Kooperatif Tipe Team Games Tournament pada Pembelajaran Matematika Kelas V Sekolah Dasar - Aguvia, Rifani Dwi; Sayekti, Ika Candra (FONDATIA, 2024)
The purpose of this research is to find a solution to the problem of low learning outcomes and the level of student activeness which is 60% still below KKM and has not been completed for fraction material. The learning method used is the Teams Games Tournament (TGT) type learning model. This research is part of Classroom Action Research (PTK), which uses two cycles, namely cycle I and cycle II to assess the application of TGT. Planning, implementing, observing, and reflecting on the learning process are part of each cycle. Students who acted as subjects of grade V students of SDN Kleco 1 Surakarta amounted to 28 students. Data were collected by observation, tests and documentation. Data analysis used descriptive, qualitative, and comparative. The data shows that the increase in student involvement and learning outcomes can be done by using a cooperative learning model with the Teams Games Tournament (TGT) format. grade V SDN Kleco 1 Surakarta the level of student activeness increased by 19.9% in cycle I 68.4% increased in cycle II to 88.3%. The class average score for students in grade V increased along with their learning outcomes in math. In cycle I 59.1 and cycle II 82.5, Regarding learning completeness, the percentage of students who are complete (80%) has been in accordance with the estimated performance indicators. The improvement in learning outcomes occurred because before learning in groups, the teacher presented the roles to each student and emphasized to them the importance of collaborating to achieve a common goal.